ANALISIS SIKAP KONSUMEN DALAM KEPUTUSAN PEMBELIAN SEPEDA MOTOR MEREK JIALING DAN VIAR DI KOTA BANDAR LAMPUNG - AW Siswo Susilo; Andy Fitriyadi Dharma Tilaar (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2010)
This study is conducted based on the fact that there are many motorcycle brands distributedin the market. The effect of economic crisis striking Indonesia caused the change of attitude patternof the customers. This condition make motorcycle manufactures rearrange marketing program whichhas been set up. Customer’s attitude toward a product has very important meaning for themanufacturer in creating marketing program, and there is general assumption that the customer’sattitude serves as strong factor to predict customer’s behavior, to predict product demand in thefuture and to develop appropriate marketing program.The purpose of this study is : (a) to determine and analyze the customer’s attitude inpurchasing JIALING and VIAR branded motorcycle; (b) to determine and analyze the effect ofcustomer’s social environment toward subjective norm in decision making of purchasing JIALINGand VIAR branded motorcycle; (c) to find out and analyze different attitude of the customer towardJIALING and VIAR branded motorcycle products.